Pemberian Kompres Hangat Jahe Untuk Menurunkan Tingkat Nyeri Pada Lansia Penderita Asam Urat - Mela Sulistyiana; Sudiarto s; Fida Dyah Puspasari (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Background: Gout is a disease where purine buildup occurs which can cause join inflammation tp the point of swelling, so that someone who has gout will definitely feel unbearable pain. Gout usually appears in the big toe, ankle, knee, and elbow areas. One of the non-pharmacological treatments to reduce pain is to use ginger warm compresses. Purpose: this study was to describe the effect of giving warm ginger compresses to reduce pain levels in elderly people with gout. Research method: case study. Result: research shows that giving ginger warm compresses can reduce the level of pain felt by Mrs. S with an initial pain scale of 7 then dropped to a pain scale of 4. Conclusion: research has the effect of warm ginger compresses to reduce the pain level of gout sufferers in Mrs. S with an initial scale of 7 to a scale of 4.